TASKS OF INTERCULTURAL EDUCATION IN THE CONDITIONS OF UKRAINIAN-TURKISH BILINGUALISM - Demianiuk, Anzhela; Isayev, Khurshud (Scientific Journal of Polonia University, 2024)
The article examines the main tasks of intercultural education in the conditions of Ukrainian-Turkish bilingualism; insignificant acculturation of children in a foreign-speaking environment was noted, since the picture of the world of Ukrainian-speaking students studying in Turkey includes a small number of Turkish components; three main groups of nominations reflecting linguistic and cultural specificity are highlighted: cultural idioms, words with an idio-ethnic aura, idioms. It was emphasized that the task of expanding the Ukrainian picture of the world with a Turkish component should be systematically solved in schools where children from Ukrainian-speaking families study. The process of acculturation is based on the communicative process. The practical implementation of bicultural education can be achieved through the joint education of Ukrainian children and children from mixed Ukrainian-Turkish families; introduction of subjects related to the national culture of the host country into the curriculum; enrichment of basic educational disciplines with national Ukrainian and Turkish issues; mandatory inclusion of linguistic and cultural information in Ukrainian and Turkish language programs; creation of electives on Turkish topics taking into account the interests of children. The article proposed attempt is to present possible directions and methods of developing the concept of TURKEY in Ukrainian language classes.